2017
DOI: 10.1007/s40477-016-0238-x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler Imaging in the evaluation of abdominal aortic pulsatility: a useful tool for the neonatologist

Abstract: (English) Sonographic cardiac evaluation of newborns with suspected aortic coarctation (AoC) should tend to demonstrate a good phasic and pulsatile flow and the absence of pressure gradient along a normally conformed aortic arch from the modified left parasternal and suprasternal echocardiographic views; these findings, however, may not necessarily rule out a more distal coarctation in the descending aorta. For this reason, the sonographic exam of newborns with suspected AoC should always include a Doppler eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In addition, the accuracy of a diaphragmatic amplitude assessment by M‐mode US can be strongly affected by the diaphragmatic subtlety of the neonate, especially in premature neonates. We considered it more feasible to measure the peak velocities of the right diaphragmatic excursions by using PW‐TDI because the diaphragmatic dome appears as a straight echogenic line, the same as the lateral mitral annulus or the abdominal aortic wall . Indeed, we measured exact time‐to‐peak velocities by sampling the muscle with the transducer lined up as parallel as possible to the diaphragmatic line moving to and from the transducer with breathing, providing a real‐time assessment of diaphragmatic kinetics, unlike M‐mode US.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the accuracy of a diaphragmatic amplitude assessment by M‐mode US can be strongly affected by the diaphragmatic subtlety of the neonate, especially in premature neonates. We considered it more feasible to measure the peak velocities of the right diaphragmatic excursions by using PW‐TDI because the diaphragmatic dome appears as a straight echogenic line, the same as the lateral mitral annulus or the abdominal aortic wall . Indeed, we measured exact time‐to‐peak velocities by sampling the muscle with the transducer lined up as parallel as possible to the diaphragmatic line moving to and from the transducer with breathing, providing a real‐time assessment of diaphragmatic kinetics, unlike M‐mode US.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that TDI could be used to evaluate arterial stiffening in humans by measuring the vessel wall motion waveforms [ 35 , 66 ]. Multiple TDI-related parameters were applied in assessing the aortic elastic properties, including wall velocities and tissue strain (TDI-ε).…”
Section: Integrating Applications Of Ultrasonography In the Assessmentioning
confidence: 99%